Analisis Tingkat Efisiensi Saluran Distribusi Komoditi Bawang Merah di Kabupaten Bandung (Coopetition : Jurnal Ilmiah Manajemen, 2024)
This research aims to address the challenges faced by shallot farmers in distributing their produce. A preliminary survey conducted in the field revealed a significant price gap between the farm and consumer levels, ranging from Rp.2,000 to Rp.4,000 per kg. Thus, the objective of this study is to identify the distribution channels for shallots in Cimaung Subdistrict, assess the efficiency levels and farmers' income across various channels, and recommend strategies for farmers to enhance their income. The research method employed is a case study with a sample size of 35 shallot farmers. The farmers were selected from the population using incidental sampling techniques. Snowball sampling was used to identify the institutions involved in the shallot distribution channel in Cimaung District. The study found that there are six type distribution channels in Cimaung Subdistrict, involving three distribution institutions: intermediary traders, wholesalers, and retailers. The type VI distribution channel was found to have the smallest efficiency value at 3.1%, while the type V distribution channel had the largest farmer share at 92.64%. (3) Farmers who use type VI distribution channels with a selling price of Rp.30,000/kg and type IV distribution channels with a price of Rp.29,167/kg obtain the highest income. (4) The following section discusses the factors that contribute to income growth.